Fiscal federalism and tax enforcement - Timm Bönke; Beate Jochimsen; Carsten Schröder (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
In many federations, fiscal equalization schemes soften fiscal imbalances across the member states. Such schemes usually imply that a member state internalizes only a small fraction of the additional tax revenue from an expansion of the state-specific tax base, while the remainder of the additional tax revenue is redistributed horizontally or vertically. We address the question as to which extent state-level authorities in such a federation under-exploit their tax bases. By means of a stylized model we show that the state authorities in such a federation have incentives to align the effective tax rates of the state residents to the internalized marginal return from a stricter enforcement of the tax law. We empirically test the model using two approaches. In a state-level approach, we explore whether the state-specific internalized marginal returns matter for the states investments in tax enforcement. In a micro-econometric approach, using OLS regressions and natural-experiments, we explore whether internalized marginal returns matter for the effectiveness of the states tax enforcement activities, captured by the tax deductions granted to tax units. All our estimates support the results from our theoretical model.
Keywords: H21; H77; C21; 330